Experimental investigation on wake and thrust characteristics of a twin-rotor horizontal axis tidal stream turbine. (August 2022) - Zhang, Jisheng; Zhou, Yudi; Lin, Xiangfeng; Wang, Guohui; Guo, Yakun; Chen, Hao
Abstract: Study on the performance of the tidal stream turbines could greatly improve tidal stream energy development. Up to date, few studies about the twin-rotor horizontal axis tidal turbines (TRHATTs) are available. In this study, laboratory experiments with a range of approaching flow velocity and yaw angles are conducted to investigate the wake structures in the lee side of the turbine. The experimental results show that there are three 'rod-liked' wakes behind the turbine, which merge into one wake further downstream. Increase of the approaching flow velocity can accelerate wake velocity recovery and enhances turbulence intensity. Correspondingly, the thrust and the fluctuation of thrust also increase. When the turbine is subjected to the yawed inflow, one side of the near wake mixing accelerates and the turbulence intensity distribution becomes asymmetric. The study shows that the thrust is slightly reduced with an increase of the yaw angle, and reaches the maximum when the yaw angle is 40°. Fluctuation range of the thrust increases with the increase of the yaw angle, and starts to decrease when the yaw angle exceeds 30°. Highlights: The thrust on the turbine decreases gradually with the increasing yaw angle. There are three 'rod-liked' wakes behind the twin-rotors and the mono-pile. Wake velocity and turbulence intensity vary sharply within 4D downstream. The yaw angle affects the shape of wake and recovery of wake velocity.